Association between albumin and short-term outcomes of unplanned early readmission emergency department patients: A retrospective cohort study - Liang Zhou; Xiaona Cai; Kunpeng Hu; Shuo Tang; Dandan Gao; Xiaojuan Zhang; Yin Wu; Li He; Bangfu Zhou; Ruoyu Wu; Zhigang Zhang (PLoS ONE, 2025)
Objective This study was a post hoc analysis of data from a retrospective cohort population. The purpose of this study was to analyze the predictive value of albumin for the short-term survival of patients with unplanned early readmission to the emergency department (ED). Methods A total of 6,249 emergency patients were enrolled in this study, including 5,368 patients (85.49%) who had been admitted for the first time and 881 patients (14.51%) with unplanned early readmission to the ED; the data were from the clinical cohort data publicly released on the Dryad website. The patients were classified on the basis of the tertile of their albumin values. Kaplan‒Meier survival curve analysis, the log-rank test and a Cox proportional hazards model were used to analyze the associations between albumin levels and 30-day mortality risk in emergency patients. The dose‒response relationship between albumin and outcome was fitted by a restricted cubic spline (RCS). Sensitivity analysis was performed on the results of the difference test by creating a multivariate Cox regression model with the forward likelihood ratio (LR) method. Results The demographic characteristics and clinical indicators of patients in the ED differed according to the number of admissions. The median albumin level of patients admitted to the hospital for the first time was greater than that of patients who were readmitted (Z = −9.642, P < 0.001). The duration of patient hospitalization was used as the follow-up time. The median length of hospitalization was 2 days (range: 1–123 days); 328 patients died within 30 days, and the all-cause mortality rate of patients with unplanned early readmission was higher than that of first-time hospitalization patients (4.49% vs. 9.86%, χ2 =44.136, P < 0.001). Kaplan–Meier survival curve analysis revealed that albumin levels were associated with 30-day mortality in all patients, first-time admitted patients, and patients with unplanned early readmission (log-rank test, P < 0.001). The multivariate Cox regression model revealed that albumin was a significant factor only in all patients combined (HR 0.93, 95% CI 0.91–0.95, P < 0.001) and in first-time admitted patients (HR 0.92, 95% CI 0.89–0.94, P < 0.001) but not in patients with unplanned early readmission (HR 0.97, 95% CI 0.93–1.01, P = 0.121). The same result was obtained with a Cox regression model in which albumin was included as a categorical variable. Sensitivity analysis revealed that the results of multivariate Cox regression analysis were reliable. Conclusion There was a specific correlation between albumin and the short-term outcome of emergency patients. Albumin levels are associated with short-term outcomes in patients admitted to the hospital for the first time, but its association with the outcomes of patients with unplanned early readmission to the ED is likely trivial.